Seasonal Influenza Vaccination of Children Induces Humoral and Cell-Mediated Immunity Beyond the Current Season: Cross-reactivity With Past and Future Strains. (28th August 2016) - Reber, Adrian J.; Kim, Jin Hyang; Coleman, Laura A.; Spencer, Sarah M.; Chung, Jessie R.; Chen, Jufu; Gargiullo, Paul; Sundaram, Maria E.; Belongia, Edward A.; Shay, David K.; Katz, Jacqueline M.; Sambhara, Suryaprakash
Abstract : Background: Influenza viruses gradually accumulate point mutations, reducing the effectiveness of prior immune protection. Methods: Children aged 9–14 years received 2010–2011 trivalent inactivated influenza vaccine (TIV). Vaccination history, hemagglutination-inhibition (HI) titers, and cell-mediated immune responses were assessed to investigate the cross-reactivity with past and future influenza virus strains. Results: 2010–2011 TIV induced significant T-cell responses and HI titers of ≥160, with a fold-rise of ≥4 and titers of ≥100 maintained for >7 months in the majority of children. Pre-existing memory B cells in these children differentiated quickly to antibody-secreting cells to the new vaccine antigens. Children vaccinated in the previous year maintained high HI titers well into 2010, demonstrating elevated HI titers against A/Perth/16/2009, the future (in 2010–2011) H3N2 component. Prior vaccination enhanced CD8 + T-cell responses to A/Perth/16/2009. Children vaccinated with the prior 2009–2010 seasonal vaccine also demonstrated higher preexisting levels of interferon γ–secreting CD4 + CD69 + T cells to 2009 pandemic influenza A(H1N1). Children previously vaccinated with 2009–2010 seasonal influenza vaccine also showed greater expansion of tumor necrosis factor α–secreting CD8 + CD69 + T cells to 2009 pandemic influenza A(H1N1) upon vaccination in the 2010–2011 season than those who were not previously vaccinated. Conclusions: Seasonal influenza viruses continuously drift, which allows them to circumvent protective immunity, but conserved epitopes provide immunological cross-reactivity in children through either vaccination directly or through prime/boost in the prior influenza season.